Five years' real-life experience with raltegravir in a large HIV centre. (April 2016) - van Halsema, Clare; Whitfield, Thomas; Lin, Naomi; Ashton, Kathryn; Torkington, Adele; Ustianowski, Andrew
Raltegravir was the first licensed integrase inhibitor. Real-life experience is informative and complements trial data. We therefore evaluated raltegravir use in adults in a large HIV treatment centre. From pharmacy and departmental HIV database records, we identified all adults taking ≥1 dose of raltegravir from first availability to the end of November 2012. Data were collected using a standardised case report form. Two hundred and fifteen individuals provided 502 patient-years (median 2.6 years/person) of raltegravir use. Of 215 individuals, 166 (77%) were male, median age 43 years; 189 (88%) were antiretroviral therapy (ART)-experienced and 26 (12%) ART-naive, with median baseline CD4 counts of 324 and 54 cells/µL, respectively. Of ten individuals using once-daily raltegravir, four, with good adherence remained virologically suppressed after a median 28 months, four stopped against medical advice, one stopped to simplify and one failed virologically. In hepatitis co-infection, 35 individuals (92 patient-years) took raltegravir without evidence of hepatotoxicity. Six women started raltegravir during pregnancy for intensification (5/6) or switch for tolerability without complications. Of ten individuals stopping raltegravir after virological failure, 2/4 with successful sequencing showed resistance. Raltegravir appears safe and effective, without evidence of toxicity above that in published trials, including in pregnancy and co-infections. Once-daily dosing seems effective where adherence is good.